Crystal structures of three representatives of a new Pfam family PF14869 (DUF4488) suggest they function in sugar binding/uptake. (12th August 2014) - Kumar, Abhinav; Punta, Marco; Axelrod, Herbert L.; Das, Debanu; Farr, Carol L.; Grant, Joanna C.; Chiu, Hsiu‐Ju; Miller, Mitchell D.; Coggill, Penelope C.; Klock, Heath E.; Elsliger, Marc‐André; Deacon, Ashley M.; et al.
Abstract Crystal structures of three members (BACOVA_00364 from Bacteroides ovatus, BACUNI_03039 from Bacteroides uniformis and BACEGG_00036 from Bacteroides eggerthii) of the Pfam domain of unknown function (DUF4488) were determined to 1.95, 1.66, and 1.81 Å resolutions, respectively. The protein structures adopt an eight‐stranded, calycin‐like, β‐barrel fold and bind an endogenous unknown ligand at one end of the β‐barrel. The amino acids interacting with the ligand are not conserved in any other protein of known structure with this particular fold. The size and chemical environment of the bound ligand suggest binding or transport of a small polar molecule(s) as a potential function for these proteins. These are the first structural representatives of a newly defined PF14869 (DUF4488) Pfam family.